Pro Memoria: Atombomben er vor ven. Den danske regerings stillingtagen til og reaktioner på atomvåbnenes integration i NATOs forsvarsstrategi 1949-1956 - Søborg Agger, Jonathan; Wolsgård, Lasse (Historisk Tidsskrift, 2013)
The Danish Government and NATO's Nuclear Defence Strategy 1949-1956Based on only recently released documents from the archives of the Royal Danish Ministry of Foreign Affairs and the Ministry of Defence, the present study demonstrates that the Danish government's acceptance of NATO's integration of nuclear weapons into its defensive strategy was less reserved, less problematic, and less hesitant than the most recent and otherwise best documented Danish research on the topic has assumed. At no point was there any Danish aversion to the strategic concept, which from 1954 included the use of both tactical and strategic nuclear devices in the defence of Western Europe - even without prior use by the Soviet Union. This by no means implies that the government was happy with the way nuclear strategy was developing. Like politicians in many other countries, Danish politicians would have preferred that the atomic bomb had never been invented. Nevertheless, the inner circle of security policy-makers held the view that prohibition of the atomic bomb without a simultaneous reduction of conventional arms would have catastrophic consequences for world peace - and for Danish security.It can be documented that from 1954 on the Danish Government acknowledged that the decision on when to use the nuclear arsenal would, and should, be taken by the president of the United States, and by him alone. If deterrence was to work, this was the only realistic situation. This, however, was not official policy. There was, indeed, nothing to be gained by relinquishing formal rights.At a meeting of NATO ministers in December 1954 Denmark did engage in the debate on political control, adamantly insisting that the decision on when to use nuclear weapons was not to be taken by NATO's military authorities. This was a crucial point for the Danish government as well as for several other governments, especially the British. But contrary to previous assumptions, the Danish government never attempted to establish concrete guidelines for political control.The leading security policy-makers understood and accepted that atomic weapons were the only realistic deterrent to a possible Soviet attack. Furthermore, the employment of tactical nuclear devices promoted the realization of a forward line of defence, thereby ensuring that Denmark would be defended. In addition, loyalty towards the Alliance as well as a realistic recognition of Denmark's limited influence contributed to acquiescence in the increasing role of nuclear arms in NATO's defensive strategy.Translated by Michael Wolfe